The Symbolic Meanings of Traditional Objects in the Mohuntingo Procession in Kabila District - Yuyun Indriani Ointu; Mohamad Karmin Baruadi; Muslimin (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
The Mohuntingo procession is a sacred birth ritual in the Gorontalo community, performed as an expression of gratitude through the ceremonial cutting of an infant’s hair. Beyond its ceremonial nature, this tradition embodies deep philosophical values reflected in each ritual stage and the symbolic use of traditional objects. Every element in the Mohuntingo procession represents the cultural worldview of the Gorontalo people, which is strongly rooted in customary practices and Islamic principles. This study provides a detailed description of the Mohuntingo stages in Kabila District and examines the symbolic meanings of the traditional objects used, including young coconut, betel nut, dulang, fragrant oil, a razor, flowers, and lu’adu. A descriptive qualitative design was employed, with data gathered through observation, interviews with traditional and religious leaders, cultural practitioners, and local residents, as well as field documentation. Data were analyzed through reduction, presentation, and interpretation while maintaining the sociocultural context of Gorontalo society. The findings reveal that each traditional object holds symbolic meanings related to purity, protection, cultural identity, life harmony, and the reinforcement of religious values. The ritual also strengthens social cohesion, deepens kinship ties, and functions as a medium for transmitting customary and Islamic values to younger generations. Overall, the study concludes that Mohuntingo is not merely a birth ritual but a cultural transmission system rich in spiritual, social, and educational significance, demonstrating the enduring relevance of Gorontalo’s cultural identity amid modernizing influences.